Experimental autoimmune uveoretinitis in the RCS rat: the influence of photoreceptor degeneration on disease expression. Issue 9 (September 1992) - Atkinson, E G; Edelsten, C; Kasp, E; Dumonde, D C
Abstract : S-antigen induced experimental autoimmune uveoretinitis (EAU) was produced in the Royal College of Surgeons (RCS) strain of rat which develops a photoreceptor dystrophy within 2 weeks of birth. Animals were sensitised at 60, 90, and 105 days of age: all animals developed disease, but onset was significantly delayed in older (105 day) animals compared with those aged 60 days at sensitisation (p 0.003). Disease was characterised by the early development of complete serous retinal detachment which resolved in a few days: the prevalence of retinal detachment was increased to 80% in dystrophic animals compared with 10% in the congenic, non-dystrophic controls (p < 0.001). Anterior uveitis was seen in 17/30 control strain eyes, but in none of 30 dystrophic eyes (p < 0.001). Genetically determined photoreceptor and retinal pigment epithelium dysfunction in the RCS rat, which may involve the local accumulation of altered S-antigen, predisposes the dystrophic strain to display an acute retinal detachment in the early stages of EAU. This phenomenon illustrates how biochemical dysfunction of a target organ may influence susceptibility, form, and severity of an experimental autoimmune disease.